School Zone Road Safety Assessment Along Urban Roads with Different Traffic Characteristics: A Case Study of Kathmandu Valley - Khanal, Aakriti; Bhatta, Bipin; Rijal, Amisha; Giri, Amrit; Marsani, Anil (International Journal on Engineering Technology, 2026)
Kathmandu Valley has emerged as Nepal’s major educational and socio-economic center and it has experienced rapid urban expansion and unplanned growth of educational institutions, resulting in increased road safety concerns around school areas. Inadequate road and pedestrian infrastructure, high traffic volumes, and high vehicle operating speeds have significantly increased the risk for school children. This study, titled “School Zone Road Safety Assessment Along Urban Roads with Different Traffic Characteristics: A Case Study of Kathmandu Valley”, assesses the safety performance of selected school zones using the International Road Assessment Program (iRAP)'s Star Rating for Schools (SR4S) methodology. Field observation was conducted to determine the key safety parameters as described by the SR4S coding guide. The assessment revealed that both school zones performed below the internationally recommended 3-star safety benchmark. It is majorly due to high traffic volume, uncontrolled vehicle speed, and sub-standard infrastructure.Based on the assessment, the study recommends scenario-based interventions that are easy to implement, such as installing speed limit signs, enforcing stricter parking regulations, enhancing curve geometry, and improving road markings and signage, to improve overall road safety.